Stomach trichobezoar (rapunzel syndrome) with iatrogenic intussusception - Yik, Y.I.; How, A.K. (Malaysian Medical Association, 2016)
We present a rare case of stomach trichobezoar complicated with iatrogenic intussusception noted intra-operatively after failed attempt of endoscopic removal in a 13-year-old girl. At presentation, she had gastric outlet obstruction with anaemia. Endoscopy established the diagnosis of trichobezoar. Surgical removal was warranted after failed endoscopic removal. Her postoperative course was uneventful. Detailed history and careful examination disclosed trichotillomania and associated trichophagia. Psychiatric referral was sought with the intention to prevent future recurrence.